2023
DOI: 10.1002/advs.202300824
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis, Necroptosis, and Pyroptosis in Gastrointestinal Cancers: The Chief Culprits of Tumor Progression and Drug Resistance

Abstract: In recent years, the incidence of gastrointestinal cancers is increasing, particularly in the younger population. Effective treatment is crucial for improving patients’ survival outcomes. Programmed cell death, regulated by various genes, plays a fundamental role in the growth and development of organisms. It is also critical for maintaining tissue and organ homeostasis and takes part in multiple pathological processes. In addition to apoptosis, there are other types of programmed cell death, such as ferroptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 218 publications
0
16
0
Order By: Relevance
“…In addition to Western blotting, the mRNA levels of ADAR1 and ZBP1 were examined in various cell lines (Figure B). It has also been previously reported that ADAR1 inhibits the necroptosis pathway by inhibiting ZBP1 to downregulate RIPK3-mediated necroptosis in cancer. ,, Consequently, other marker proteins in necroptosis, such as RIPK1 and RIPK3, were monitored. While RIPK1 exhibited similar expression levels in both normal and cancer cells, in keeping with a previous report, RIPK3 expression was found to be absent in most of the cell lines derived from solid tumors, such as HeLa cells.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to Western blotting, the mRNA levels of ADAR1 and ZBP1 were examined in various cell lines (Figure B). It has also been previously reported that ADAR1 inhibits the necroptosis pathway by inhibiting ZBP1 to downregulate RIPK3-mediated necroptosis in cancer. ,, Consequently, other marker proteins in necroptosis, such as RIPK1 and RIPK3, were monitored. While RIPK1 exhibited similar expression levels in both normal and cancer cells, in keeping with a previous report, RIPK3 expression was found to be absent in most of the cell lines derived from solid tumors, such as HeLa cells.…”
Section: Resultsmentioning
confidence: 97%
“…Our investigation has unearthed intriguing facets of this interaction. Notably, the interaction between Z-DNA and ADAR1 has been found to impede the function of ZBP1, resulting in the suppression of apoptotic cascades via the caspase pathway and the inhibition of necroptotic processes through the MLKL pathway within the context of cancer biology. ,, Concomitantly, ADAR1 binding exerts a regulatory influence on immune responses, acting as a negative modulator of intracellular innate immunity, chiefly by interfering with the MDA5/MAV5 axis, thereby fostering the progression of cancer cells. , Using the Z-PROTAC approach, we achieved the targeted degradation of ADAR1, while leaving ZBP1 unaffected, specifically within cancer cells. Moreover, Z-PROTAC manipulation has been shown to induce PANoptotic responses, encompassing both apoptosis and necroptosis, exclusively within cancerous cellular contexts as opposed to normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Copper is an intracellular trace element essential for a variety of biological functions. However, an excess of copper ions is toxic and causes cell death, which is newly defined as cuproptosis by Tsvetkov et al 1 Different from other known cell death pathways, such as apoptosis, 2,3 necroptosis, 4,5 pyroptosis, 6,7 and ferroptosis, 8,9 cuproptosis was induced by intracellular copper ions accumulation which triggers the aggregation of mitochondrial lipoylated proteins, thereby resulting in proteotoxic stress and consequent cell death. 10−12 To be specific, in the copper ions-overloaded cells, copper ions bound to lipoylated proteins (especially dihydrolipoamide S-acetyltransferase, DLAT) of the mitochondrial tricarboxylic acid (TCA) cycle and thus facilitated the aggregation of these proteins, 13−15 triggering cuproptosis of cancer cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Copper is an intracellular trace element essential for a variety of biological functions. However, an excess of copper ions is toxic and causes cell death, which is newly defined as cuproptosis by Tsvetkov et al Different from other known cell death pathways, such as apoptosis, , necroptosis, , pyroptosis, , and ferroptosis, , cuproptosis was induced by intracellular copper ions accumulation which triggers the aggregation of mitochondrial lipoylated proteins, thereby resulting in proteotoxic stress and consequent cell death. To be specific, in the copper ions-overloaded cells, copper ions bound to lipoylated proteins (especially dihydrolipoamide S-acetyltransferase, DLAT) of the mitochondrial tricarboxylic acid (TCA) cycle and thus facilitated the aggregation of these proteins, triggering cuproptosis of cancer cells. Since first reported in 2022, this copper-dependent cuproptosis has sparked tremendous attention in cancer therapy and a few studies of cuproptosis-based cancer therapy have recently been reported. ,, However, the application of cuproptosis in tumor treatment suffers from several challenges: (a) the intracellular copper level was too low to realize therapeutic activity, (b) nonselectivity and potential systemic toxicity of copper ions resulted in off-target toxicities and unpredictable side effects, , and (c) there is difficulty in transporting free copper ions into cancer cells because excess copper ions were discharged out of the cells through copper exporters like ATP7A and ATP7B .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the genetic complexity and heterogeneity of OS, the process of chemoresistance is an intricate biological process involving several molecular interactions. Cancer cells can become resistant to chemotherapy drugs through various mechanisms: (1) impaired DNA repair; (2) reduced drug transport and increased drug efflux; (3) cell apoptosis, invasion, migration, and cycle; (4) autophagy; (5) signaling pathway activation; (6) tumor microenvironment (TME) and angiogenesis (Hueso et al, 2021;Li et al, 2024;Zhu & Li, 2023). The absence of powerful diagnostic markers or therapeutic targets severely limits the prognosis of OS patients.…”
Section: Introductionmentioning
confidence: 99%